2019
DOI: 10.3390/nu11010194
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina Liquid Extract Protects against Fibrosis Related to Non-Alcoholic Steatohepatitis and Increases Ursodeoxycholic Acid

Abstract: Non-alcoholic steatohepatitis (NASH) is characterized by an excess of lipids and oxidative stress in the liver. Spirulina was reported to possess hypolipemic and antioxidative effects and might counteract NASH development. C57Bl/6J mice were fed a western diet (WD) during 25 weeks with or without spirulina liquid extract (SLE) at 2 different doses (WDS1 and WDS2 groups) in drinking water. Liver histology, inflammation, and oxidative stress were assessed as well as glucose tolerance status, lipid metabolism, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…Signals were quantified by measuring the total amplitude of the spectra obtained, after correction of baseline. For superoxide anion evaluation, the instrument settings were the same as for the NO measurement, except of the sweep time, which was 60 s. The signals were quantified by calculating the height of the central peak of the spectra, after the correction of baseline, as previously described [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Signals were quantified by measuring the total amplitude of the spectra obtained, after correction of baseline. For superoxide anion evaluation, the instrument settings were the same as for the NO measurement, except of the sweep time, which was 60 s. The signals were quantified by calculating the height of the central peak of the spectra, after the correction of baseline, as previously described [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…We measured O 2 − levels in tissues as described previously [ 26 ]. The tissue was incubated for 45 min at 37°C in a Krebs-HEPES solution containing 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine (CMH, 500 mM, Noxygen; Denzlingen, Germany) as spin probe, deferoxamine (25 mM, Sigma-Aldrich), and diethyldithiocarbamate (DETC, 5 mM, Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies also show that Spirulina lipids are major factors responsible for health beneficial effects [33][34][35][36]. Coué et al reported that the liquid Spirulina extract effectively attenuates hepatic fibrosis, inflammation, oxidative stress, and insulin resistance in C57Bl/6J mice fed a western-style diet [37]. The main polyunsaturated fatty acids (PUFAs) of Spirulina lipids is gamma-linolenic acid (GLA, C18:3n-6).…”
Section: Introductionmentioning
confidence: 99%